2021
DOI: 10.17582/journal.vsrr/2021.7.2.121.128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Welfare and Health Conditions on Working Donkeys in Benadir Region, Somalia

Abstract: Activity 5.Selection of target groups and determination of preferred dissemination pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several more studies have reported ages ranging from 3 to 13 years [15,20,32]. The most common ages of donkeys assessed in this study were 5 and 9 years old, which is similar to M o h a m e d et al [23].…”
Section: Discussionsupporting
confidence: 85%
“…Several more studies have reported ages ranging from 3 to 13 years [15,20,32]. The most common ages of donkeys assessed in this study were 5 and 9 years old, which is similar to M o h a m e d et al [23].…”
Section: Discussionsupporting
confidence: 85%
“…Integumentary trauma was present in nearly 90% of the mules assessed, which is higher than seen in other studies. It is generally accepted that harnessing creates many of the injuries in working equids (Ali et al, 2016;Farhat et al, 2020;Frohlich et al, 2020;Luna et al, 2017;Mohamed et al, 2021) when the harness equipment is not well fitted to the mule's body (Cousquer, 2015). Lack of harness care and cleaning can be associated with trauma from harnessing equipment (Burn et al, 2008;Farhat et al, 2020), and the use of non-breathable materials (particularly in such dusty, gritty conditions) would exacerbate rubbing when mules sweat or work in wet conditions.…”
Section: Discussionmentioning
confidence: 99%